Cultura, estudos literários e grande tempo - Brait, Beth; Lopes-Dugnani, Bruna; Cruz Pistori, Maria Helena; Stella, Paulo Rogério; Gontijo Rosa, Carlos (Bakhtiniana. Revista de Estudos do Discurso, 2023)
Editorial 18.4